Perencanaan Strategi dan Pemasaran PT ESP dalam Memanfaatkan Tandan Kosong Kelapa Sawit (TKKS) sebagai Alternatif Bahan Bakar Terbarukan - Gultom, Martina; Hamdi, Edi; Iskandar, Muhammad Dhafi; Negoro, Dimas Angga (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research explores the technical and economic feasibility of utilizing Empty Palm Oil Bunches (EPB) waste from the palm oil industry for energy production. The research method is descriptive qualitative which focuses on problems based on facts. Data collection was carried out through in-depth interviews with PT ESP management, observations and internal company documentation as well as to collect input from various stakeholders. The results of this study concluded that the SWOT analysis carried out showed that PT ESP had strengths in access to raw materials (EPB) and opportunities. in the green energy market, although challenges such as government regulations and complex processing technologies still need to be faced. The marketing strategy implemented by PT ESP must focus on promoting sustainability, with an emphasis on environmental benefits and reducing carbon emissions. Potential target markets include clean energy-oriented industries and governments that support renewable energy policies. By utilizing EFB as an alternative fuel, PT ESP has the opportunity to lead innovation in the renewable energy sector while supporting the sustainability of the palm oil industry. A mature strategy and strong policy support will be key factors for success.